Smp38 MAP Kinase Regulation in Schistosoma mansoni: Roles in Survival, Oviposition, and Protection Against Oxidative Stress - Avelar, Lívia das Graças Amaral; Gava, Sandra Grossi; Neves, Renata Heisler; Silva, Mercedes Carolina Soares; Araújo, Neusa; Tavares, Naiara Clemente; Khal, Assmaa El; Mattos, Ana Carolina Alves; Machado-Silva, José Roberto; Oliveira, Guilherme; Mourão, Marina de Moraes (Frontiers in Immunology, 2019)
Eukaryotic protein kinases (ePKs) are good medical targets for drug development in different biological systems. ePKs participate in many cellular processes, including the p38 MAPK regulation of homeostasis upon oxidative stress. We propose to assess the role of Smp38 MAPK signaling pathway in S. mansoni development and protection against oxidative stress, parasite survival, and also to elucidate which target genes have their expression regulated by Smp38 MAPK. After a significant reduction of up to 84% in the transcription level by Smp38 MAPK gene knockdown, no visible phenotypic changes were reported in schistosomula in culture. The development of adult worms was tested in vivo in mice infected with the Smp38 knocked-down schistosomula. It was observed that Smp38 MAPK has an essential role in the transformation and survival of the parasites as a low number of adult worms was recovered. Smp38 knockdown also resulted in decreased egg production, damaged adult worm tegument, and underdeveloped ovaries in females. Furthermore, only ~13% of the eggs produced developed into mature eggs. Our results suggest that inhibition of the Smp38 MAPK activity interfere in parasites protection against reactive oxygen species. Smp38 knockdown in adult worms resulted in 80% reduction in transcription levels on the 10th day, with consequent reduction of 94.4% in oviposition in vitro. In order to search for Smp38 MAPK pathway regulated genes, we used an RNASeq approach and identified 1,154 DEGs in Smp38 knockdown schistosomula. A substantial proportion of DEGs encode proteins with unknown function. The results indicate that Smp38 regulates essential signaling pathways for the establishment of parasite homeostasis, including genes related to antioxidant defense, structural composition of ribosomes, spliceosomes, cytoskeleton, as well as, purine and pyrimidine metabolism pathways. Our data show that the Smp38 MAPK signaling pathway is a critical route for parasite development and may present attractive therapeutic targets for the treatment and control of schistosomiasis.